Unexpectedly minor nitrous oxide emissions from fluvial networks draining permafrost catchments of the East Qinghai-Tibet Plateau - Zhang, Liwei; Zhang, Sibo; Xia, Xinghui; Battin, Tom J.; Liu, Shaoda; Wang, Qingrui; Liu, Ran; Yang, Zhifeng; Ni, Jinren; Stanley, Emily H. (Nature communications, 2022)
Streams and rivers emit substantial amounts of nitrous oxide (N 2 O) and are therefore an essential component of global nitrogen (N) cycle. Permafrost soils store a large reservoir of dormant N that, upon thawing, can enter fluvial networks and partly degrade to N 2 O, yet the role of waterborne release of N 2 O in permafrost regions is unclear. Here we report N 2 O concentrations and fluxes during different seasons between 2016 and 2018 in four watersheds on the East Qinghai-Tibet Plateau. Thawing permafrost soils are known to emit N 2 O at a high rate, but permafrost rivers draining the East Qinghai-Tibet Plateau behave as unexpectedly minor sources of atmospheric N 2 O. Such low N 2 O fluxes are associated with low riverine dissolved inorganic N (DIN) after terrestrial plant uptake, unfavorable conditions for N 2 O generation via denitrification, and low N 2 O yield due to a small ratio of nitrite reductase: nitrous oxide reductase in these rivers. We estimate fluvial N 2 O emissions of 0.432 − 0.463 Gg N 2 O-N yr −1 from permafrost landscapes on the entire Qinghai-Tibet Plateau, which is marginal (~0.15%) given their areal contribution to global streams and rivers (0.7%). However, we suggest that these permafrost-affected rivers can shift from minor sources to strong emitters in the warmer future, likely giving rise to the permafrost non-carbon feedback that intensifies warming. Permafrost soils can be substantial sources of nitrous oxide (N 2 O) to the atmosphere, but no data exist on the N 2 O footprints of permafrost rivers. Here, the authors show that alpine permafrost rivers are unexpectedly small sources of atmospheric N 2 O at present.